Women's Simple Characters for the Downfall of the Mayor of Casterbridge in Thomas Hardy's the Mayor of Casterbridge - M. Ridwan; Atiq Mohammad Romdlon; Abu Fanani; Machfud Muhamad Sodiq; Fathur Rohim (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
There are a lot of studies about characters, most of which are about characters dealing with the good and bad characters as the result of the study. This study challenges the previous studies above that study on characters not merely deal with and bad but deal with survival through the characters. In Thomas Hardy’s the Mayor of Casterbridge, I study about women’s simple character for the downfall of the Mayor of Casterbriidge. Using New Criticism focusing on the characterization as well as close reading as a method, this study shows the result that the four women: Susan Henchard, Lucetta, Elizabeth Jane, and the furmity woman are above the greatness of the Mayor of Casterbridge through their simple character; Susan Henchard by her simple and natural act for the sake of her daughter future, Lucetta by her simple act to marry another man for fear of the terrible marriage with the Mayor of Casterbridge, Elizabeth Jane with her simple character to ignore the Mayor of Casterbridge for tricking her real father, and the furmity woman with her simple testimony of the terrible wife sale by the Mayor of Casterbridge. All women’s simple characters put the Mayor of Casterbridge in complete downfall in love and in business. In conclusion, though being a great man in the Casterbridge, Michael Henchard undergoes a complete downfall by the simplicity of the characters of the women. Finally, simple character is worth studying to prevent people to be arrogant.